Black women, writing, and identity: Migrations of the subject - Boyce Davies, Carole (Routledge, 1994)
Black Women Writing and Identity is an exciting work by one of the most imaginative and acute writers around. The book explores a complex and fascinating set of interrelated issues, establishing the significance of such wide-ranging subjects as: * re-mapping, re-naming and cultural crossings * tourist ideologies and playful world travelling * gender, heritage and identity * African women's writing and resistance to domination * marginality, effacement and decentering * gender, language and the politics of location Carole Boyce-Davies is at the forefront of attempts to broaden the discourse surrounding the representation of and by black women and women of colour. Black Women Writing and Identity represents an extraordinary achievement in this field, taking our understanding of identity, location and representation to new levels.
Keywords: approches et analyses; arts; discipline; fem1000; femmes* noires; féminismes noirs; littérature; premier cycle; ressource en ligne; thématiques; écriture des femmes*; études littéraires; études postcoloniales

Reading black, reading feminist: A critical anthology - Gates, Henry Louis (Meridian Book, 1987)
A unique and comprehensive collection of 26 literary essays that provides real evidence of the rich cultural history of black women in America. Black women’s writing has finally emerged as one of the most dynamic fields of American literature. Here, leading literary critics—both male and female, black and white—look at fiction, nonfiction, poetry, slave narratives, and autobiographies in a totally new way. In essence, they reconstruct a literary history that documents black women as artists, intellectuals, symbol makers, teachers, and survivors. Important writers whose work and lives are explored include Toni Morrison, Gloria Gaynor, Maya Angelou, and Alice Walker, and the fascinating list of essays range from Nellie Y. McKay’s “The Souls of Black Women Folk in the Writings of W. E. B. Du Bois” to Jewelle L Gomez’s very personal tribute to Lorraine Hansberry as a dramatist and crusader for social justice. Henry Louis Gates Jr., the editor of this anthology and a noted authority on African-American literature, has provided a thought-provoking introduction that celebrates the experience of “reading black, reading feminist.” A penetrating look at women’s writing from a unique perspective, this superb collection brings to light the rich heritage of literary creativity among African-American women.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; arts; discipline; fem1000; feminismes noirs; femmes* noires; pratiques féministes; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; états-unis; études littéraires